2009
DOI: 10.1017/s0266466609990326
|View full text |Cite
|
Sign up to set email alerts
|

GLS-Based Unit Root Tests With Multiple Structural Breaks Under Both the Null and the Alternative Hypotheses

Abstract: Perron (1989, Econometrica 57, 1361–1401) introduced unit root tests valid when a break at a known date in the trend function of a time series is present. In particular, they allow a break under both the null and alternative hypotheses and are invariant to the magnitude of the shift in level and/or slope. The subsequent literature devised procedures valid in the case of an unknown break date. However, in doing so most research, in particular the commonly used test of Zivot and Andrews (1992, Journal of Busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
214
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(231 citation statements)
references
References 36 publications
2
214
0
15
Order By: Relevance
“…This work is in line with Kim and Perron (2006) and Carrion-i Silvestre, Kim, and Perron (2007), who recognize that structural breaks in the deterministic trend occur whether the noise component is stationary or has a unit root.…”
Section: Introductionsupporting
confidence: 84%
“…This work is in line with Kim and Perron (2006) and Carrion-i Silvestre, Kim, and Perron (2007), who recognize that structural breaks in the deterministic trend occur whether the noise component is stationary or has a unit root.…”
Section: Introductionsupporting
confidence: 84%
“…2001). 9 Using instead the annualized quarter-on-quarter changes, {ln(P t ) − ln(P t−1 )} 400, leads to very similar an alternative measure of inflation, we calculated the percentage changes for the GDP-deflator. The implied GDP-deflator was calculated based on the ratio of the nominal GDP (series GDP) and the real GDP (series GDPC1) in chained 2005 dollars.…”
Section: The Datamentioning
confidence: 99%
“…To deal with these issues, we use a two-step method advocated by Perron (2007), Kim and Perron (2007), Harris et al (2007) and Carrion-i- Silvestre et al (2008). In the first step, we pretest the pollution series of interest for structural change using Exp-W RFS which is valid whether the series is DS or TS.…”
mentioning
confidence: 99%
“…If the pre-test does not reject, we proceed as if we know a break does not occur and use the ADF-GLS test for a unit root that does not allow for a break. Harris et al (2007), Kim and Perron (2007) and Carrion-i- Silvestre et al (2008) showed that such a two step procedure leads to unit root tests with good size and power properties whether a break occurs or not.…”
mentioning
confidence: 99%